Anaerobic degradation kinetics of a cholesteryl ester - Gutiérrez, S (Water science and technology : a journal of the International Association on Water Pollution Research, 2003)
The most important components of wool scouring effluent grease are esters of sterols. Cholesteryl palmitate (CP) is the main ester in this grease. In this paper, the influence of the ester concentration in the anaerobic digestion and the relative rate of the different degradation steps, are studied. The experiment was carried out to measure methane production in the anaerobic degradation of acetate, palmitic acid (PA) and CP. A first-order kinetic model was assumed for hydrolysis and Monod models were assumed for both the methanogenic and acetogenic steps. Maximum hydrolysis rate was found to be around 20 times faster than the maximum methanogenic reaction rate during the experience. The lanolin emulsion drop size effect was also evaluated employing fine and coarse stock lanolin emulsions and no adapted sludge. Concentrations of 13.7 to 4.6 gCOD x l(-1) were employed. In a previous study, the effect of palmitic acid emulsion size was found important when similar sludge was tested. When esters are degraded, a significant effect of drop size on the degradation rate was not found. The difference between CP and PA emulsions behavior could be due to the fact that cholesterol produced during the ester degradation has a protective effect on the sludge